Family Rehabilitation Training by Jinyun Rehabilitation Platform in Patients with Ankylosing Spondylitis Treated by Chinese Medicine Fumigation Combined with Muscle Energy Technology - Longbin SHEN; Hui OUYANG; Dongling WU; Wenhao XIE (康复学报)
Objective:To observe the effect of treatment of Chinese medicine fumigation and muscle energy technology, combined with family rehabilitation training by Jinyun rehabilitation platform on dysfunction improvement of patients with ankylosing spondylitis (AS), and explore a hospital-family integrated treatment approach that is feasible for dysfunction improvement of AS patients.Methods:A total of 80 AS patients with active stage who met the diagnostic and inclusion criteria were randomly assigned to the experimental group (n=42) and the control group (n=38). The control group was treated with Chinese medicine fumigation, muscle energy technology and anti-inflammatory painkillers. The treatment of Chinese medicine fumigation for AS patients was about 30 minutes each time, and the treatment of muscle energy technology was about 40 minutes each time. The frequency of the two kinds of treatment was once a day, five times a week, the first week of each month was chosed as the treatment time, and there should be six weeks of treatment time in six months. The anti-inflammatory painkiller was oral celecoxib, 200 mg each time, twice a day, and the treatment lasted for three weeks. The experimental group received the family rehabilitation training management of Jingyun rehabilitation platform on the base of the control group. The AS patients completed the action as prompted by the platform, then recorded a video to the platform; the rehabilitation therapists entered the backstage and checked the completion of the action; the AS patients could enter into next stage of clinical treatment and rehabilitation training when their movements were qualified. The family rehabilitation training was divided into two phases, in the first phase, the treatment time of three months lasted about 30 minutes each time, three times a day; in the second phase, the treatment time of three months lasted about 30 minutes each time, two times a day. After treatment, the visual analogue score (VAS), rang of motion (ROM), muscle strength, Bath AS disease activity index (BASDAI), Bath AS functional index (BASFI), Schober test score, erythrocyte sedimentation rate (ESR) and C reactive protein (CRP) were compared between the two groups.Results:Before treatment, there was no significant difference in VAS, ROM, muscle strength, BASDAI, BASFI, Schober score, ESR and CRP between the two groups (P> 0.05). After treatment, the VAS, BASDAI, BASFI, ESR and CRP were decreased (P< 0.01), and the ROM, muscle strength and Schober score were increased in two groups compared with before treatment (P< 0.01). After treatment, the VAS, BASDAI, BASFI, ESR and CRP in the experimental group were lower than those of the control group (P< 0.05), and the cervical vertebrae ROM, lumbar vertebrae ROM, muscle strength and Schober score were higher than those of the control group (P< 0.05).Conclusion:Chinese medicine fumigation combined with muscle energy technology is effective for treating low back pain of AS patients. Under these treatments, adding Jingyun rehabilitation platform for family rehabilitation training can effectively improve the treatment effect of low back pain, promote the overall recovery of the patient's spinal function, and help the AS patients to achieve a hospital-family integrated treatment approach.